Primary lack of efficacy of infliximab therapy for rheumatoid arthritis: pharmacokinetic characterization and assessment of switching to tocilizumab - Mori, Shunsuke (Springer Japan, 2011)
To characterize primary failure to infliximab and determine the efficacy of switching to tocilizumab in patients with rheumatoid arthritis (RA), we examined 24 RA patients who had started on infliximab therapy (3 mg/kg) as their first biological agent. Nine of the 24 patients were found to be primary nonresponders, defined as patients who had never achieved a 20% clinical improvement according to the American College of Rheumatology criteria (ACR20) during induction therapy. The remaining 15 patients had achieved an ACR20 response to infliximab, without any relapses, for at least the first 14 weeks. A higher baseline health assessment questionnaire score was markedly associated with primary unresponsiveness to infliximab (p = 0.0005). Six of the 9 primary nonresponders showed rapid clearance of infliximab: their trough concentrations of infliximab were under 1 μg/ml. The other 3 were classified as exhibiting the residual type of unresponsiveness, which was defined as unresponsiveness in patients who maintained serum infliximab levels above 1 μg/ml. Human antichimeric antibody was not detected in the rapid-clearance nonresponders. Dose escalation (5 mg/kg) was insufficiently effective. Primary nonresponders to infliximab were started on tocilizumab therapy (8 mg/kg, every 4 weeks), and their responses were assessed after 24 weeks of this second attempt at therapy. All the nonresponders, except for a single rapid-clearance patient, had achieved an ACR20 clinical improvement at the time of assessment. In conclusion, primary nonresponders to infliximab can be classified into rapid-clearance and residual types, based on their trough concentrations of infliximab, but both types of nonresponders seem to benefit from an early decision to discontinue infliximab therapy and switch to tocilizumab.